Meltwater production in Antarctic blue-ice areas: sensitivity to changes in atmospheric forcing - Liston, Glen E.; Bruland, Oddbjørn; Winther, Jan-Gunnar; Elvehøy, Hallgeir; Sand, Knut (Polar Research, 1999)
In the near coastal regions of Dronning Maud Land, Antarctica, below-surface ice-melt in blue-ice areas has been observed. The low scattering coefficients of the large-grained blue-ice allow penetration of solar radiation, thus providing an energy source below the ice surface. The sub-surface meltwater is significant enough to show up on remote-sensing imagery in the form of ice-covered lakes. Adjacent snow-accumulation areas have much higher scattering coefficients and consequently limit solar radiation penetration in these regions. These snow and ice surfaces are generally below freezing, and little surface melting occurs. To assess the response of these melt features to changes in atmospheric forcings such as cloudiness, air temperature, and snow accumulation, a physically-based model of the coupled atmosphere, radiation, snow, and blue-ice system has been developed. The model consists of a heat transfer equation with a spectrally-dependent solar-radiation source term. The penetration of radiation into the snow and blue-ice depends on the surface albedo, and the snow and blue-ice grain size and density. Model simulations show that ice melt occurring in this area is sensitive to potential variations in atmospheric forcing. Under certain conditions more traditional surface melting occurs and, under other conditions, the existing melt processes can be shut down completely. In light of the sensitivity of this system to variations in atmospheric forcing, and the ability to view melt-related features using remote sensing, a tool exists to efficiently monitor variations in Antarctic coastal climate.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; glasiologi; innlandsis; isshelf; smelting

Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Mass balance and dynamics on Jutulstraumen ice stream - Hagen, Jon Ove; Melvold, Kjetil (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; akkumulasjon; glasiologi; isshelf; isstrøm; klimaendringer; snø

Hot water drilling near Filchner station, Ronne ice shelf - Orheim, Olav; Østerhus, Svein; Melvold, Kjetil; Eiken, Trond; Thomsen, Henrik Højmark; Winther, Jan-Gunnar; Bævre, Halvor (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Antarktis; NARE 1992/93; glasiologi; havstrømmer; isshelf; oseanografi; vannmasser

Changing mass balance of the Filchner ice shelf due to climate variations - Solås, Monica Kristensen; Eggenfellner, Heinrich (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isshelf; klimaendringer

Detailed studies of bottom freezing under an iceshelf and mapping of accumulation by use of multi-frequency pulse-aperture radar - Erlingsson, Bjørn; Gjessing, Yngvar; Hamran, Svein Erik; Holmlund, Per (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; ekspedisjoner; georadar; isshelf; topografi

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Proximal sub ice-shelf sedimentation Jutulgryta, East Antarctica - Solheim, Anders (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; glasiologi; isshelf

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Observations of ice shelf water at the southern Weddel sea shelf break - Foldvik, Arne; Gammelsrød, Tor; Nordlund, Nina; Nytun, Kjell (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: NARE 1989/90; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isshelf; oseanografi

The tides of the southern Weddell Sea - Foldvik, Arne; Middleton, Jason H; Foster, Theodore D (Deep Sea Research Part A. Oceanographic Research Papers, 1990)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; tidevann

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Studies on, and underneath, the Ice Shelf Fimbulisen - Orheim, Olav; Hagen, Jon Ove; Østerhus, Svein; Sætrang, Arne (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; isshelf

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser